Fiqh Muamalah Sharia Pawnshop - Widy Hastuty HS; Andri Soemitra (International Journal of Economics, Social Science, Entrepreneurship and Technology (IJESET), 2022)
Pawn is a form of guarantee in a loan agreement.even this product can be said to be a superior product in every Islamic financial institution. Transactions in this pawnshop must be strictly monitored so that each transaction can provide benefits. Many studies have been conducted on the application of fiqh muamalah pawnshops, especially in pawnshops or Islamic banking financial institutions. The current research will group the research topics of fiqh muamalah pawnshops to find out the existing research map so that it can be seen what has been researched and further research opportunities for the expansion of research and development of muamalah fiqh. By using qualitative research with content analysis and focus discussion groups with economists, the articles used were 15 articles published in journals in Indonesia from 2018 to 2021, the topic of this muamalah fiqh research consisted of 5 topics, namely (1) provisions sharia law regarding pawnshops, (2) the suitability of the DSN MUI fatwa transaction for pawnshops (3) public interest in pawning, (4) products in sharia pawnshops, and (5) marketing strategies for sharia pawnshops